Quality of life of postgraduate students stricto sensu in dentistry and sociodemographic factors - Cinthia Nara Gadelha TEIXEIRA; Maria Imaculada de Queiroz RODRIGUES; Paulo Goberlanio de Barros SILVA; Myrna Maria Arcanjo FROTA; Maria Eneide Leitão de ALMEIDA (Universidade Estadual Paulista, 2017)
Abstract Introduction Quality of life (QL) is subjective and must be based on a multidimensional construct and on positive and negative factors in the individual's life. Objective The objective of this study was to evaluate the QL of the students of the Postgraduate Program in Dentistry (PPGO) of the Federal University of Ceará. Material and method Cross-sectional study with a quantitative approach, conducted with 88 students regularly enrolled in PPGO. The QL was measured by the World Health Organization Questionnaire for Quality of Life-bref (WHOQOL-bref). For a better analysis of the QL scores, they were categorized into three levels: dissatisfaction, uncertainty and satisfaction. A multinomial logistic regression model was used. Result The majority of the respondents (55.7%) was classified in the area of satisfaction with QL, with 14,05 total average scores, corresponding to 62.8% of the total. By associating the socio-demographic data with the categories of analysis of QL, it was observed relevant in single students (p=0.005), those who considered themselves religious (p=0.041) and those who did not have a postgraduate scholarship (p=0.025), being evaluated in the area of dissatisfaction/uncertainty about the QL. Conclusion It was concluded that marital status, religion and scholarship in postgraduate school were relevant in the QL of stricto sensu postgraduate students in Dentistry.